AN INNOVATIVE MODEL FOR FORMING FINANCIAL LITERACY: AN INNOVATIVE MODEL FOR FORMING FINANCIAL LITERACY - Zagorcheva-Koycheva, Denitsa (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
This scientific article presents an innovative model for the formation of financial literacy. The model is based on cognitive development, focusing on the contact environment with which children/individuals of different age groups interact. The model presents the understanding of money as a personal value, which should be formed in the relevant age range. Financial literacy, through upbringing and training, should be built on the basis of the cognitive development and mental capabilities of children and adults.